2023
DOI: 10.1111/jcal.12801
|View full text |Cite
|
Sign up to set email alerts
|

Towards a fuller picture: Triangulation and integration of the measurement of self‐regulated learning based on trace and think aloud data

Abstract: Background: Many learners struggle to productively self-regulate their learning. To support the learners' self-regulated learning (SRL) and boost their achievement, it is essential to understand the cognitive and metacognitive processes that underlie SRL.To measure these processes, contemporary SRL researchers have largely utilized think aloud or trace data, however, not without challenges.Objectives: In this paper, we present the findings of a study that investigated how concurrent analysis and integration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Being able to measure SRL in think-aloud at scale is particularly relevant given the two approaches-behavioral log data and thinkaloud protocols-appear to complement each other rather than being substitutive, as noted in [19]. In their study, they show that SRL behaviors, such as orientation and elaboration, were more likely to be detected in behavioral log data than in think-aloud protocols.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Being able to measure SRL in think-aloud at scale is particularly relevant given the two approaches-behavioral log data and thinkaloud protocols-appear to complement each other rather than being substitutive, as noted in [19]. In their study, they show that SRL behaviors, such as orientation and elaboration, were more likely to be detected in behavioral log data than in think-aloud protocols.…”
Section: Introductionmentioning
confidence: 87%
“…Think-aloud protocols (TAPs) are an important approach for investigating SRL during problem-solving and have been widely used in prior research [9,26,28,37]. Previous studies not only demonstrate TAPs as a valid approach to measure SRL but also underlines its importance in capturing SRL in a more comprehensive way, complementing behavioral log data in SRL measurement [19]. However, TAPs require researchers to manually code students' verbalizations, which presents challenges in scalability.…”
Section: Main Findings and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding implies that future work should (a) incorporate information from ITS log data (i.e., whether a Tutor chat recommendation would lead to a correct attempt) into the prediction of the BERT model and (b) include training data examples of contextually incorrect constructive messages by Tutors into its sample. Indeed, prior work found similar integrations of log data into natural language for inference of self-regulated to be effective [20]. Similarly, nascent work found that the exclusion of problem-solving context in tutoring systems likely limits the accuracy of classifiers of selfregulation process stages based on natural language [72].…”
Section: Limitations In Constructive Tutor Messagesmentioning
confidence: 99%
“…We collected think-aloud from students working with ITS for stoichiometry chemistry, a domain that, to the best of our knowledge, has not been investigated via fine-grained SRL codes. As suggested in prior work [19,42], think-aloud protocols provide valid measures on students' use of SRL because they capture an immediate window into students' cognitive and metacognitive processes as opposed to predefined categories in self-report questionnaires. The rich accounts of SRL in think-aloud data are especially useful when limited inferences can be drawn from behavioral logs.…”
Section: Introductionmentioning
confidence: 99%